2019
DOI: 10.1111/obr.12970
|View full text |Cite
|
Sign up to set email alerts
|

The obesity paradox for outcomes in atrial fibrillation: Evidence from an exposure‐effect analysis of prospective studies

Abstract: The impact of obesity on the prognosis of atrial fibrillation (AF) remains controversial. We conducted an exposure-effect meta-analysis of prospective studies to clarify the relationship between body mass index (BMI) and outcomes in patients with AF. The Cochrane Library, PubMed, and Embase databases were searched through May 1, 2019. Summary relative risks (RRs) were calculated using random-effects models. Nonlinear associations were explored using restricted cubic spline models. Twenty publications involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 74 publications
3
43
5
1
Order By: Relevance
“…The present study found that an increase in BMI is an important risk factor for IS in NVAF patients. Previous studies have shown that BMI is negatively correlated with IS in AF patients [27], which is contrary to the results of the present study. At present, the relationship between obesity and IS remains controversial [27][28].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study found that an increase in BMI is an important risk factor for IS in NVAF patients. Previous studies have shown that BMI is negatively correlated with IS in AF patients [27], which is contrary to the results of the present study. At present, the relationship between obesity and IS remains controversial [27][28].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown that BMI is negatively correlated with IS in AF patients [27], which is contrary to the results of the present study. At present, the relationship between obesity and IS remains controversial [27][28]. Large-scale and prospective studies are needed to further explore the impact of BMI on adverse event outcomes in AF patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown that BMI is negatively correlated with IS in AF patients [42], which is contrary to the results of the present study. At present, the relationship between obesity and IS remains controversial [42][43]. Large sample, multicentre and prospective studies are needed to further explore the relationship between BMI and serum lipids and the in uence of this relationship on adverse event outcomes in AF patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Obesity has been reported as an independent risk factor for new‐onset AF, being associated with a 20% higher risk of AF than normal weight 4 . However, a number of clinical studies and meta‐analyses found that compared with patients with normal weight, patients with overweight or obesity did not have worse or even better outcomes among patients with AF, known as the “obesity paradox.” 5‐7 This phenomenon was also found in patients with obesity and other diseases; for example, in studies examining the rate of complications in patients undergoing percutaneous coronary intervention, the rate of complications was paradoxically found to decrease in patients with mild/moderate obesity 8,9 …”
Section: Introductionmentioning
confidence: 93%